# If S1,

S = n [First term is 1, common ratio 1; so sum to n terms = 1 + 1 + 1 + - - = n]
ii) S
= (2ⁿ - 1)/(2 - 1) = (2ⁿ - 1)
iii) S
= (3ⁿ - 1)/2
iv) S
= (4ⁿ - 1)/3 ..
v) So, S
+ S + 2S + 3S + - - - - + (n - 1)Sⁿ =
= n + (2ⁿ - 1) + (3ⁿ - 1) + (4ⁿ - 1) + - - - - - - - + (nⁿ - 1)
= n + ( - 1 - 1 - 1 .... to n - 1 terms) + (2ⁿ + 3ⁿ + 4ⁿ + .... + nⁿ) =
= n - (n - 1) + (2ⁿ + 3ⁿ + 4ⁿ + .... + nⁿ) = 1 + (2ⁿ + 3ⁿ + 4ⁿ + .... + nⁿ)
= 1ⁿ + 2ⁿ + 3ⁿ + 4ⁿ + .... + nⁿ [Proved]

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

A person has 2 paRD Sharma - Mathematics

The sum of the seRD Sharma - Mathematics

How many terms ofRD Sharma - Mathematics

If <span lang="ENRD Sharma - Mathematics

Let anRD Sharma - Mathematics

Find the sum of 2RD Sharma - Mathematics

If <span lang="ENRS Aggarwal - Mathematics

Find the sum (41 RS Aggarwal - Mathematics

Find the sum (2 +RS Aggarwal - Mathematics

If<span lang="EN-RS Aggarwal - Mathematics